Immunodynamics of explanted human tumors for immuno‐oncology. Issue 1 (29th December 2020) - Dubuisson, Agathe; Fahrner, Jean‐Eudes; Goubet, Anne‐Gaëlle; Terrisse, Safae; Voisin, Nicolas; Bayard, Charles; Lofek, Sebastien; Drubay, Damien; Bredel, Delphine; Mouraud, Séverine; Susini, Sandrine; Cogdill, Alexandria; et al.
Abstract: Decision making in immuno‐oncology is pivotal to adapt therapy to the tumor microenvironment (TME) of the patient among the numerous options of monoclonal antibodies or small molecules. Predicting the best combinatorial regimen remains an unmet medical need. Here, we report a multiplex functional and dynamic immuno‐assay based on the capacity of the TME to respond to ex vivo stimulation with twelve immunomodulators including immune checkpoint inhibitors (ICI) in 43 human primary tumors. This " in sitro" ( in situ / in vitro ) assay has the potential to predict unresponsiveness to anti‐PD‐1 mAbs, and to detect the most appropriate and personalized combinatorial regimen. Prospective clinical trials are awaited to validate this in sitro assay. Synopsis: To predict cancer resistance to PD‐1 blockade and design suitable combinations of immunomodulators, a 60‐h functional in sitro assay was set up in 43 tumors that allowed calculation of the "Immune Reactivity Score (IRS)" based on 17 TCR‐dependent‐ cytokines/chemokines. Primary resistance to PD‐1 blockade could be predicted in vitro and in vivo with 70% accuracy. CXCL10 was the best in situ predictor of IRS score and response to PD‐1 blockade in patients. 50% of primary resistance to PD‐1 blockade could be overcome by a personalized combinatorial regimen. Hypo‐responders to PD‐1 blockade could be prevented by combining anti‐PD‐1 and anti‐KIR mAbs. Abstract : To predict cancer resistance to PD‐1 blockade and design suitable combinations of immunomodulators, a 60‐h functional in sitro assay was set up in 43 tumors that allowed calculation of the "Immune Reactivity Score (IRS)" based on 17 TCR‐dependent‐ cytokines/chemokines.